A prospective trial of dynamic contrast-enhanced MRI perfusion and fluorine-18 FDG PET-CT in differentiating brain tumor progression from radiation injury after cranial irradiation. Issue 6 (19th December 2015) - Hatzoglou, Vaios; Yang, T. Jonathan; Omuro, Antonio; Gavrilovic, Igor; Ulaner, Gary; Rubel, Jennifer; Schneider, Taylor; Woo, Kaitlin M.; Zhang, Zhigang; Peck, Kyung K.; Beal, Kathryn; Young, Robert J.
Abstract: Background: The aim of this study was to assess the effectiveness of fluorine-18 fluorodeoxyglucose (FDG) PET-CT and dynamic contrast-enhanced (DCE) MRI in differentiating tumor progression and radiation injury in patients with indeterminate enhancing lesions after radiation therapy (RT) for brain malignancies. Methods: Patients with indeterminate enhancing brain lesions on conventional MRI after RT underwent brain DCE-MRI and PET-CT in a prospective trial. Informed consent was obtained. Lesion outcomes were determined by histopathology and/or clinical and imaging follow-up. Metrics obtained included plasma volume (Vp) and volume transfer coefficient (K trans ) from DCE-MRI, and maximum standardized uptake value (SUVmax ) from PET-CT; lesion-to-normal brain ratios of all metrics were calculated. The Wilcoxon rank sum test and receiver operating characteristic analysis were performed. Results: The study included 53 patients (29 treated for 29 gliomas and 24 treated for 26 brain metastases). Progression was determined in 38/55 (69%) indeterminate lesions and radiation injury in 17 (31%). Vpratio (VP lesion /VP normal brain, P < .001), K trans ratio ( P = .002), and SUVratio ( P = .002) correlated significantly with diagnosis of progression versus radiation injury. Progressing lesions exhibited higher values of all 3 metrics compared with radiation injury. Vpratio had the highest accuracy in determining progression (area under the curve = 0.87), with 92% sensitivity and 77% specificity using the optimal, retrospectively determined threshold of 2.1. When Vpratio was combined with K trans ratio (optimal threshold 3.6), accuracy increased to 94%. Conclusions: Vpratio was the most effective metric for distinguishing progression from radiation injury. Adding K trans ratio to Vpratio further improved accuracy. DCE-MRI is an effective imaging technique for evaluating nonspecific enhancing intracranial lesions after RT.